2017
DOI: 10.1021/jacs.7b05722
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Abstraction Thermodynamics of a μ-1,2-Superoxo Dicopper(II) Complex

Abstract: Pyrazolate-based μ-1,2-peroxo dicopper(II) complex 1 undergoes clean 1e oxidation at low potential (-0.59 V vs Fc/Fc) to yield the rather stable μ-1,2-superoxo dicopper(II) complex 3, which was characterized by spectroscopic methods (ν̃(O-O) = 1070 cm, Δ(O-O) = -59 cm) and analyzed by DFT calculations. 3 is also formed via H-atom abstraction from the corresponding μ-1,1-hydroperoxo dicopper(II) complex 2, while 3 itself is able to abstract H-atoms from weaker X-H bonds such as TEMPO-H to re-form 2. Kinetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 27 publications
11
71
0
Order By: Relevance
“…Recently Meyer et al have reported the reaction of μ‐1,2‐superoxo dicopper(II) complex with TEMPO‐H, which resulted in formation of a μ‐1,1‐hydroperoxo dicopper(II) complex via HAT mechanism. The reaction exhibited activation parameters of Δ H ‡ = 9.03 ± 0.4 kcal · mol –1 and Δ S ‡ = –26.76 ± 1.7 cal · K –1 · mol –1 , which are close to our activation parameters . Kieber‐Emmons et al recently reported the reaction of a dicopper(II)‐μ‐oxo adduct with TEMPOH, which resulted in the formation of a dicopper(I,II)‐μ‐hydroxo adduct via a concerted HAT mechanism.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Recently Meyer et al have reported the reaction of μ‐1,2‐superoxo dicopper(II) complex with TEMPO‐H, which resulted in formation of a μ‐1,1‐hydroperoxo dicopper(II) complex via HAT mechanism. The reaction exhibited activation parameters of Δ H ‡ = 9.03 ± 0.4 kcal · mol –1 and Δ S ‡ = –26.76 ± 1.7 cal · K –1 · mol –1 , which are close to our activation parameters . Kieber‐Emmons et al recently reported the reaction of a dicopper(II)‐μ‐oxo adduct with TEMPOH, which resulted in the formation of a dicopper(I,II)‐μ‐hydroxo adduct via a concerted HAT mechanism.…”
Section: Resultssupporting
confidence: 83%
“…[60] Thus, the O-H bond dissociation energy of 6 is suggested to be around 80 kcal·mol -1 . Of note, the O-H bond dissociation energy of Meyer's μ-1,1-hydroperoxo dicopper(II) complex was estimated as 72 kcal·mol -1 [58] and Kieber-Emmons's dicopper(I,II)-μ-hydroxo complex as 77.2 kcal·mol -1 . [59] Based on the observed reactivity of the superoxide copper(II) complexes, 4 and 4Ј, a comparison of their reactivity can be made.…”
Section: Articlementioning
confidence: 99%
“…A great deal of information about structures and spectroscopic features of metal–oxygen centers can and have been obtained from synthetic models of enzymatic active sites by using fast‐time acquisition set‐ups, organic solvents, and low temperatures . However, redox potentials and electron‐transfer properties of such active species are scarce; that is, for products of O 2 stepwise reduction, in particular for copper–oxygen systems . Nonetheless, such information is important for the development of efficient devices in the energy research area such as fuel cells (O 2 ‐reduction), solar photoelectrochemical cells (water oxidation), and organic lithium–air batteries…”
Section: Methodsmentioning
confidence: 99%
“…As previously discussed, this derives from stronger electron‐withdrawing effects of the dicobalt(III) core assuming that charge at the HOMO is localized on the dioxygen core for both peroxo complexes. Interestingly, superoxo/peroxo dicopper complexes bearing a dinucleating pyrazolate‐bridged bis(tacn) (tacn=triazacyclononane) ligand have been very recently studied at much higher temperature (273 K) in acetonitrile by CV . A quasi‐reversible system was found at −0.59 V vs. Fc and ascribed to a ligand‐centered redox process according to UV/Vis spectroscopic experiments driven by chemical reagents.…”
Section: Methodsmentioning
confidence: 99%
“…[24] In particular, superoxo bridged diCu II have been reported to perform the abstraction of H atom from organic substrates. [25] Even though this was not investigated by the authors, this dicopper system is of potential interest for catalytic oxidation by O 2 with the assistance of electrochemistry. Indeed, it is expected that the formation of the peroxo bridged complex 3 + or of the superoxo bridged diCu II intermediate 2 2+ can be controlled upon polarization of the oxygenated solution at E < 0.02 V or E > 0.07 V, respectively.…”
Section: Dinuclear Complexesmentioning
confidence: 99%